2021
DOI: 10.4103/ijem.ijem_396_20
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile in Infant

Abstract: Introduction: Alteration in lipid parameters at birth has a strong association with the development of cardiovascular disease in later life. Material and Methods: Sixty-one infants below the age of 6 months underwent evaluation of lipid parameters. The infants studied were categorized into two groups of ≤4 and >4 weeks of age, wherein their lipid parameters were compared. Results: The normal distribution of lipid parameters of infants <6 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Lipid profling has an irreplaceable role in the assessment of dyslipidemia [9]. Previous studies suggested an independent relationship between childhood and adulthood serum lipid levels [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Lipid profling has an irreplaceable role in the assessment of dyslipidemia [9]. Previous studies suggested an independent relationship between childhood and adulthood serum lipid levels [10,11].…”
Section: Introductionmentioning
confidence: 99%